Dispersion of carbon nanotubes in aqueous solutions containing poly(diallyldimethylammonium chloride) - Li, D; Wang, H; Zhu, J; Wang, X; Lu, L; Yang, X (Journal of materials science letters, 2003)
The unique structure and properties of carbon nanotubes (CNTs) have led to a range of potential applications. However, unmodified CNTs are subject to aggregation into packed ropes or entangled networks due to strong intertube van der Waals attraction, which acts as an obstacle to most applications. Thus, there is interest in developing methods that will enable dispersion and separation of CNTs. One strategy to improve the dispersion of CNTs in solvents is to modify the CNT surface chemically, which usually involves a two-step chemical reaction process, which oxidizes the surface carbon atoms to carboxylic acid groups and then bonds them covalently to polymeric or long chain organic molecules through esterification or amidation reactions of the carboxylic acid. However, this process is time-consuming and the chemical treatment may damage the structure of pristine nanotubes. Recently, Bandyopadhyaya et al. reported a very simple procedure to disperse entangled single-wall carbon nanotubes into individual, well-separated tubes in aqueous solutions using a highly branched natural polymer, Gum Arabic, as a dispersing reagent. Chemical modification of CNTs is not needed in this process. The dispersal mechanism is based on the steric repulsion between the polymer-coated tubes. In this letter, we report that another polymer, poly(diallyldimethylammonium chloride) (PDMA) can be directly used to disperse multiple-wall carbon nanotubes in aqueous solutions.